Hubungan Karakteristik dengan Kualitas Hidup Orang Tua yang Mengasuh Anak dengan Retardasi Mental di SlB Negeri Wiradesa Kabupaten Pekalongan - Mahadewi, Celine; Mustikawati, Neti (Universitas Malahayati, 2023)
ABSTRACT Parents of mentally retarded children who are unable to overcome problems in parenting may experience changes in quality of life. Factors affecting quality of life consist of gender, age, education, occupation, income, marital status,and length of care. This study aimed to determine the relationship between characteristics and the quality of life of parents who look after children with mentalretardation at SLBN Wiradesa, Pekalongan Regency. This research was a correlational study with a cross sectional approach. The sampling technique being used was proportional random sampling. The sample of this study were 110 parents who took care of children with mental retardation grade 1 to 6 at SLBN Wiradesa, Pekalongan Regency. Their quality of life was measured by the World Health Organization Quality of Life-BREF (WHOQOL- BREF) questionnaire. The data were analyzed by the Lambda and Spearman correlation tests. The results showed that most of the respondents were female (70.0%), aged 36-45 years (60.9%), had primary school education (40.9%), worked (52.7%), had income that lower than the minimum wage of Pekalongan (77.3%), married (87.3%), and were caring for 10-15 years (67.3%). Lambda and Spearman tests results showed that there was a significant correlation between sex (p value 0.026), age (p value 0.035), education (p value 0.000), occupation (p value 0.043), income (p value 0.005), and length of care (p value 0.038) with the quality of life of the parents looking after children with mental retardation at SLBN Wiradesa, Pekalongan Regency. However, there was no significant correlation between marital status (p value 0.404) and the quality of life of the respondents. Nurses could provide interventions to improve the quality of life of the parents who looked after children with mental retardation. Keywords: Characteristics, Quality of life, Mental Retardation ABSTRAK Orang tua anak retardasi mental yang tidak mampu mengatasi masalah dalam mengasuh anak dapat mengalami perubahan kualitas hidup. Faktor yang mempengaruhi kualitas hidup seperti, jenis kelamin, usia, pendidikan, pekerjaan, penghasilan, status perkawinan, lama merawat. Penelitian ini bertujuan untuk mengetahui hubungan karakteristik dengan kualitas hidup orang tua yang mengasuh anak dengan retardasi mental di SLB Negeri Wiradesa Kabupaten Pekalongan. Penelitian ini merupakan penelitian korelasional dengan pendekatan cross sectional. Teknik pengambilan sampel menggunakan proportional random sampling. Sampel penelitian ini adalah orang tua yang mengasuh anak retardasi mental kelas 1 sampai 6 di SLB Negeri Wiradesa Kabupaten Pekalongan sebanyak 110 responden. Kualitas hidup diukur menggunakan kuesioner World Health Organization Quality of Life-BREF (WHOQOL-BREF). Data dianalisis menggunakan uji korelasi Lambda dan Spearman. Hasil penelitian didapatkan bahwa sebagian besar responden berjenis kelamin perempuan (70,0%), berusia 36-45 tahun (60,9%), berpendidikan SD (40,9%), bekerja (52,7%), penghasilan kurang dari UMK Pekalongan (77,3%), berstatus kawin (87,3%), lama merawat 10-15 tahun (67,3%). Hasil uji lambda dan spearman didapatkan ada hubungan signifikan jenis kelamin (p value 0,026), usia (p value 0,035), pendidikan (p value 0,000), pekerjaan (p value 0,043), penghasilan (p value 0,005), lama merawat (p value 0,038) dengan kualitas hidup orang tua yang mengasuh anak dengan retardasi mental di SLB Negeri Wiradesa Kabupaten Pekalongan. Tidak ada hubungan signifikan status perkawinan (p value 0,404) dengan kualitas hidup orang tua yang mengasuh anak dengan retardasi mental di SLB Negeri Wiradesa Kabupaten Pekalongan. Perawat dapat memberikan intervensi untuk meningkatkan kualitas hidup orang tua yang mengasuh anak retardasi mental. Kata Kunci: Karakteristik, Kualitas hidup, Retardasi Mental